THE EFFECT OF PRODUCT PLACEMENT IN MOVIES AND CELEBRITY ENDORSEMENT ON CONSUMER PURCHASE INTENTION OF SAMSUNG SMARTPHONE IN MANADO - Tangkuman, Ridsa Septiyan; Saerang, David P.E. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Abstract: Information and communication technology has made great strides in recent years which also had an effect on advertising such as product placement and celebrity endorsement. Smartphone is one of products that is often to be found on advertising media. This study aims to analyze the effects of product placement in movies and celebrity on consumer purchase with Samsung smartphone as its case study. This is a causal type of research which uses primary data obtained from questionnaires and uses ordinal regression analysis. The population observed is people in Manado who have purchased Samsung smartphone products with 110 respondents as the sample size. The result of this study shows that product placement and celebrity endorsement have significant effects on consumer purchase intention. To increase consumer purchase intention, the recommendations for Smartphone Company are to maintain exposure, high profile/star liking, product familiarity, and movie involvement on product placement in movies as well as consistently show physical attractiveness, celebrity congruence, trustworthiness, and expertise on celebrity endorsement which motivate purchases. Keywords: consumer purchase intention, advertising, product placement, celebrity endorsement